Penyuluhan Hukum: Kajian Yuridis tentang Hukum Pidana Mati, Pembenahan dan Dampak pada Masyarakat di Fakultas Hukum Universitas Tjut Nyak Dhien - Dahris Siregar (Fakultas Ilmu Budaya Universitas Lancang Kuning, 2023)
The death penalty is a problem issue that contains many controversies, For this reason, through this subject matter grew ideas or ideas to be more detailed so as to get data so that in this service by conducting legal counseling using research methods in the form of research techniques using normative law, specifically, analysis-based research approaches to theories, concepts, and reviewing laws and regulations related to the theme this devotion. Many people's views that the death penalty is the final verdict in court where they consider the execution of the death penalty shall constitute a direct sanction. So it is necessary to improve the death penalty, so that everyone with different statuses knows and understands it so that everyone can have equal access before the law. With the availability of legal advice activities on the death penalty at the law faculty as an implementation of the program of knowledge contained in the curriculum of the faculty of law, Tjut Nyak Dhien University, so that students are expected to understand the legal provisions and implementation of the death penalty and its effect on human rights.